2021
DOI: 10.1016/j.neo.2020.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Does the proteasome inhibitor bortezomib sensitize to DNA-damaging therapy in gastroenteropancreatic neuroendocrine neoplasms? – A preclinical assessment in vitro and in vivo

Abstract: Background: Well-differentiated gastroenteropancreatic neuroendocrine neoplasms are rare tumors with a slow proliferation. They are virtually resistant to many DNA-damaging therapeutic approaches, such as chemo- and external beam therapy, which might be overcome by DNA damage inhibition induced by proteasome inhibitors such as bortezomib. Methods and results: In this study, we assessed several combined treatment modalities in vitro and in viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 114 publications
1
10
0
Order By: Relevance
“…Based on the promising radiolabeling and in vitro experiments of the complexes in human serum and in the presence of a competitor ligand, L1-PEG 2 -TATE was synthesized and radiolabeled with [ 177 Lu]­Lu 3+ (Figure S29) and [ 225 Ac]­Ac 3+ (Figure S30) and compared with the radiolabeled analogues of DOTA-TATE (Figures S29,S30). For this purpose, all the four radiolabeled conjugates were investigated regarding their lipophilicity and binding affinity in SSTR2-positive murine pheochromocytoma (MPC) and human pancreatic carcinoid tumor (BON-SSTR2+) cell lines (BON-SSTR2+ is a genetically modified BON cell line transfected with human SSTR2) . The radiotoxicity of the [ 225 Ac]­Ac-conjugates was studied using a colony-forming assay in BON-SSTR2+.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the promising radiolabeling and in vitro experiments of the complexes in human serum and in the presence of a competitor ligand, L1-PEG 2 -TATE was synthesized and radiolabeled with [ 177 Lu]­Lu 3+ (Figure S29) and [ 225 Ac]­Ac 3+ (Figure S30) and compared with the radiolabeled analogues of DOTA-TATE (Figures S29,S30). For this purpose, all the four radiolabeled conjugates were investigated regarding their lipophilicity and binding affinity in SSTR2-positive murine pheochromocytoma (MPC) and human pancreatic carcinoid tumor (BON-SSTR2+) cell lines (BON-SSTR2+ is a genetically modified BON cell line transfected with human SSTR2) . The radiotoxicity of the [ 225 Ac]­Ac-conjugates was studied using a colony-forming assay in BON-SSTR2+.…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, all the four radiolabeled conjugates were investigated regarding their lipophilicity and binding affinity in SSTR2-positive murine pheochromocytoma (MPC) and human pancreatic carcinoid tumor (BON-SSTR2+) cell lines (BON-SSTR2+ is a genetically modified BON cell line transfected with human SSTR2). 66 The radiotoxicity of the [ 225 Ac]Ac-conjugates was studied using a colony-forming assay in BON-SSTR2+. The biodistribution, uptake, and accumulation pattern of the [ 177 Lu]Lu complexes were investigated by SPECT in MPCbearing mice over 7 d since this is a particularly wellestablished model at our facilities with respect other TATE studies.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Since proteasomes are overexpressed during the disease phase, it has been shown that treatment with BTZ stimulates the degradation of anti-apoptotic proteins while preventing the degradation of pro-apoptotic ones [ 4 , 5 , 6 , 7 ]. Apart from multiple myeloma, investigations evaluated this drug both in vitro and in vivo against other types of disease including pancreatic, prostatic or ovarian cancers, glioma, and squamous cell carcinoma, and the reported results highlighted an important anticancer activity [ 8 , 9 , 10 , 11 ]. Another important property reported in the specialized literature regarding BTZ is the possibility to increase the sensitivity of chemo-resistant multiple myeloma cell lines to chemotherapeutic agents such as melphalan and doxorubicin [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on own previous studies and data from other groups, the model appears suitable for efficient initial in vivo screening of the biodistribution of novel radiolabeled compounds prior to the evaluation in small animals [ 7 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. However, testing for target specificity of a radiolabeled tracer by blocking studies has not yet been demonstrated in the CAM model.…”
Section: Introductionmentioning
confidence: 99%